Climate change and spatial justice in coastal planning in Cuba and Brazil (2020)
This article uses the category of spatial justice as an analytical variable to explore the coastal planning of Cuba and Brazil, in the face of the challenge of climate change. The research was conducted using a qualitative methodology, applying the technique of content analysis to instruments of physical planning, based on spatial justice indicators provided in the study. These included territorial boundaries, uses of coastal space, environmental conflicts, public participation, urban insecurity, climate migration, and social exclusion, which enabled integration of coastal planning elements in the dimensions of space, policies, and tensions in different socio-economic contexts. New variables are added to the concept of spatial justice and it is shown that this constitutes an analytical category, which, expressed through coastal planning, puts both countries in better conditions to face the impacts of climate change